Study of Low-grade Chronic Inflammatory Markers in Men with Central Obesity: Cathepsin S was Correlated with Waist Circumference - Adriana Todingrante; Mansyur Arif; Uleng Bahrun; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: There is a prevalence increase of overweight and obesity in Indonesia. Central obesity can lead a variety of chronic diseases through the inflammatory process. There are some markers for low-grade chronic inflammatory, such as cathepsin S, high sensitivity C-reactive protein (hs-CRP), interleukin-1- beta (IL-1β). To our current interest that central obesity can lead to various chronic diseases through the inflammatory process, we conducted a study to investigate correlation of Cathepsin S, hs-CRP, IL-1β in men with central obesity.METHODS: A cross-sectional study was conducted. Seventy-eight selected subjects were examined to collect anthropometric data and prepared for sample collection. Collected samples were processed for the following biochemical analyses: fasting glucose, high density lipoprotein (HDL)-cholesterol, triglyceride, serum glutamic oxaloacetic transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), cathepsin S, hs-CRP, and IL-1β. Data distribution and variable correlation were then statistically analyzed.RESULTS: There were significant correlations between waist circumference (WC) and cathepsin S (p=0.030; r=0.214), hs-CRP and cathepsin S (p=0.007; r=0.276), triglyceride and IL-1β (p=0.019; r=-0.235), WC and systolic blood pressure (SBP) (p=0.003; r=-0.312), WC and fasting glucose (p=0.000; r=0.380), WC and body mass index (BMI) (p=0.000; r=0.708).CONCLUSION: Our study showed that cathepsin S was correlated with central obesity, suggesting that cathepsin S could be a potential inflammatory marker in central obesity in the future.KEYWORDS: obesity, inflammation, hs-CRP, cathepsin S, IL-1β, waist circumference